Genre out of bounds: Fluidity of an analytical term - Zlatko Knežević (University of Belgrade, 2016)
In this article we have shown the changes that happen with genre and it's forms when it is externalized in reality. In order to better explain and illustrate that process, we have used the theories about genre as a point of fixation of reality that were crafted by Mikhail Bakhtin, a russian formalist. Through a very special process of classificaiton on a hybrid body of narratives, we have seen how rigid and one-sided process of classification, which treats genre as a category fixed in time and space, ultimately damages our analysis of folklore materials.